Derivation And Inflection Word Formation Used In Al Jazeera News - Ismah Nurngaini; Dwi Puji Hastuti; Ria Andriani (Wanastra: Jurnal Bahasa dan Sastra, 2019)
New word formation cannot be avoided in the making sentences, paragraphs, and also to speak, because words are part of the language which develops interaction between individuals in a society as human communication. The nature of communication are verbal communication (oral and writing) and non verbal communication (sign language and symbols). People often use media in verbal communication, such as written media or mass media (newspaper, magazines, billboards, tabloids and banners). This research analyzed about the structure of words contained in the article Al Jazeera News entitled “Syria’s Refuge Children: Future lost to the war” which uses derivation and inflection word formation process. This research aims to know how word formation occurs and identifies how many new words are formed by derivation and inflection processes. Descriptive qualitative method uses in this research. It begins by reading theories of word formation which related to journal and books, determine the article, furthermore classifies the words that contain derivation and inflection process. From the both word formation process that used (derivation and inflection) in analyzing the article, the result of the study found inflection is mostly used, because in the article required grammatical function that contained in inflection.  Keywords: Derivation, Inflection, Word formation process